Pengaruh Risiko Kredit Dan Risiko Likuiditas Terhadap Kinerja Keuangan - Aprilia Nur Agnia; Egi Gumala Sari (Program Studi Akuntansi Sekolah Tinggi Ilmu Ekonomi Tri Bhakti, 2023)
Purpose: This study aims to determine the effect of Credit Risk and Liquidity Risk on Financial Performance. Design/methodology/approach: This research uses quantitative data, the sample in this study is basic financial sector bank which are listed on the Indonesia Stock Exchange in the period 2018 – 2022 as many as 27 companies. The analysis technique used to test the hypothesis is multiple regression analysis using Eviews 9 software. Findings: The results of this study indicate that Credit Risk has a negative and statistically significant effect on Financial Performance and Credit Risk has a negative and statistically significant effect on Financial Performance. Originality/value: This research discusses financial performance and other factors such as credit risk and liquidity risk which focuses on banking sector companies listed on the Indonesian stock exchange. This research uses a fixed effect model as a measurement of financial performance.